Detection of photosynthetic herbicides: algal growth inhibition test vs. electrochemical photosystem II biosensor - Masojídek, Jiří; Souček, Pavel; Máchová, Jana; Frolík, Jan; Klem, Karel; Malý, Jan (Ecotoxicology and environmental safety, 2011)
We compared a novel PSII-biosensor assay with a standard algal growth inhibition test for detection of photosynthetic herbicides--diuron, atrazine and isoproturon in liquid samples. To evaluate the convenience and sensitivity, values of the parameters EC50 and LOD and the duration of assays were compared. The biosensor assay was made with an electrochemical biosensor toxicity analyser with immobilised Photosystem II (PSII) complex. Using the PSII-biosensor assay, higher sensitivity (LOD) to herbicides (10(-8)-10(-9)M) was achieved as compared to standard algal growth inhibition tests (about 10(-7)M). The results of both assays showed a good correlation as concerns their EC50 values while the interval of detectable concentrations is about twice wider for PSII-biosensor. A proposed measurement protocol includes the reference standard of phytotoxicity (RSP). The main advantage of the PSII-biosensor assay is that it can be completed in about 1h and is by 1-2 orders more sensitive than standard algal growth inhibition test, which takes 72 h.
Keywords: roztoky; Toxicity Tests; herbicidy; Diuron; chemické látky znečišťující vodu; Water Pollutants, Chemical; Reproducibility of Results; diuron; Time Factors; časové faktory; Photosynthesis; Chlorophyta; Sensitivity and Specificity; testy toxicity; Photosystem II Protein Complex; fotosyntéza; senzitivita a specificita; Biosensing Techniques; fenylmočovinové sloučeniny; fotosystém II (proteinový komplex); Solutions; reprodukovatelnost výsledků; atrazin; Atrazine; biosenzitivní techniky; Phenylurea Compounds; Herbicides